Aural Plaques in Crossbred Working Horses - Schade, Jackson; Aguiar, Fabiana Carolina de; Silva, Matheus Cesar da; Silva, Tíffany Christiny Emmerich da; Casa, Mariana da Silva; Traverso, Sandra Davi; Muller, Thiago Rinaldi; Fonteque, Joandes Henrique (Acta Scientiae Veterinariae, 2017)
Background: The aural plaque is a papillomatosis variant that occurs in the inner surface of the auricular pavilion of equine. The disease is associated with economic losses in the equine sector, since it reduces the commercial value of the severely affected animals. However, there are few studies evaluating the occurrence of aural plaques in different breeds and equine populations in Brazil and in other countries. The aim of the present study was to evaluate the frequency, clinical and histological characteristics of the aural plaques in working horses from Lages, SC, Brazil. Materials, Methods & Results: Seventy-three crossbreed equines were used, including 48 males and 25 females between 1 and 25 years old, and that were used as working horses (traction) in the urban perimeter in the city of Lages, SC. The findings related to breed, age, sex, presence or absence of compatible lesions with aural plaques, anatomical location and lesion characteristics were evaluated and annotated. The lesions were photographed and drawn on paper to determine the size and distribution in the ear and were reevaluated for a period of two months with an interval of 30 days between each evaluation. The number of aural plaques was determined by manual counting in each auricular pavilion, which were divided into four quadrants (left and right upper, right and left lower). When the plaque was located in the median region of the quadrants, it was described in the region of the greatest location. To evaluate the histopathologic features, three equines that bearer typical lesions of aural plate were submitted to a biopsy. The statistical analysis of the data was performed through the descriptive analysis, and the chi-square test was used to identify the relationship between sex, presence or not of aural plaque and anatomical location of the lesions, and Analysis of Variance (ANOVA) followed by the Tukey’s test to determine the most affected quadrant, being accepted a level of significance of 5%. The frequency of affected animals by aural plaques was 56.16% (41/73), being 68% (17/25) females and 50% (24/48) males, with no predilection for sex. The superficial, depigmented and punctate lesions frequently were the most observed, being unilaterals in 63.41% (26/41) and bilaterals in 36.59% (15/41) of the animals. There was a difference for the distribution of the unilateral or bilateral lesions and the upper quadrants of the inner face of the ear frequently were the most affected. The regression of the size or number of plaques was not observed during the period of clinical follow-up. Besides, it was not observed significant increase in lesion size or appearance of new aural plaques during the evaluation period. Pain or itching were not associated with the lesions. The histopathological characteristics consisted in pronounced hyperplasia of the epidermis, deepening to the dermis, diffuse moderate orthokeratotic hyperkeratinization and acanthosis. Discussion: The high frequency of aural plaques in the study may be related to the work environment and breeding of these animals. However, more studies are needed to evaluate the epidemiological characteristics of this disease in raised and used for traction horses in the urban environment. The arrangement of the plaques on the surface of the ear was higher in the regions of the upper quadrants, suggesting that this distribution may be related to the greater exposure and access of the region to the viral transmission through insects and arthropods implicated as vectors. No regression and no increase in size or appearance of the new aural plaques were also described in previous studies. Besides, the absence of pain or itching associated with the lesions confirm which the lesions are asymptomatic. Clinical and histopathological characteristics were similar to those previously described in horses of the other breeds.